Visible Light Communication System Using Silicon Photocell for Energy Gathering and Data Receiving - Xiongbin Chen; Chengyu Min; Junqing Guo (International Journal of Optics)
Silicon photocell acts as the detector and energy convertor in the VLC system. The system model was set up and simulated in Matlab/Simulink environment. A 10 Hz square wave was modulated on LED and restored in voltage mode at the receiver. An energy gathering and signal detecting system was demonstrated at the baud rate of 19200, and the DC signal is about 2.77 V and AC signal is around 410 mV.